2018
DOI: 10.2139/ssrn.3351112
|View full text |Cite
|
Sign up to set email alerts
|

Is the Affordable Care Act Affecting Retirement Yet?

Abstract: We analyze whether the Affordable Care Act (ACA) has affected labor supply of older Americans using data that span more than four years after the policy's implementation in 2014. We find no changes in labor supply of older Americans either in response to subsidized marketplace coverage, which became available nationally in 2014, or in response to the expansion of Medicaid eligibility in some states but not others. We analyze multiple dimensions of labor supply -labor force participation; employment; full-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…However, the current findings suggest that many older adults aged 50 to 64 years still worry about maintaining employer-sponsored insurance and keep a job for that reason, perhaps because of concerns about affordability of other health insurance options. Although other studies have found no change in labor force participation or early retirement related to ACA Marketplace or Medicaid expansion coverage, these findings suggest that the ACA may not have fully eliminated job lock for individuals aged 50 to 64 years who remain employed.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…However, the current findings suggest that many older adults aged 50 to 64 years still worry about maintaining employer-sponsored insurance and keep a job for that reason, perhaps because of concerns about affordability of other health insurance options. Although other studies have found no change in labor force participation or early retirement related to ACA Marketplace or Medicaid expansion coverage, these findings suggest that the ACA may not have fully eliminated job lock for individuals aged 50 to 64 years who remain employed.…”
Section: Discussioncontrasting
confidence: 75%
“…Prior studies of this age group have primarily focused on tracking the uninsured rate, which has decreased from 15% in 2010 to 6% in 2015 after implementation of the ACA's major coverage provisions, 12 and likely continued to decrease in later years. 14 One 2014 survey 15 conducted among all nonelderly adults found limited numeracy and literacy among many adults across socioeconomic strata and found that nearly one-half of individuals with these limitations had difficulty navigating the process of selecting a health insurance plan. Before passage of the ACA, McWilliams and colleagues 16 found increased health care utilization and costs after acquiring Medicare coverage at age 65 years among previously uninsured adults with a history of diabetes, hypertension, heart disease, or stroke, compared with adults with those conditions who were previously insured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation